Checklist and distribution of ladybirds (Coleoptera, Coccinellidae) in Iranian provinces - Biranvand, Amir; Fekrat, Lida; Větrovec, Jaroslav; Ghobari, Hamed; Hamidi, Elnaz; Khormizi, Mehdi Zare; Azadbakht, Nader; Nedvěd, Oldřich; Romasi, Fatemeh; Ceryngier, Piotr (Zootaxa, 2024)
Although checklists of the Iranian ladybird beetles (Coleoptera: Coccinellidae) have been made twice in recent years, they have a number of shortcomings. Moreover, since these checklist were published, several ladybird species have been added to the Iranian fauna and several previously reported have been excluded. We therefore compiled an updated checklist of Coccinellidae found in Iran and its individual provinces based on available literature and previously unpublished records. The unpublished data allowed the addition of one species, Hyperaspis guttulata Fairmaire, 1870, to the Iranian fauna. On the other hand, some species previously reported from Iran are unlikely to occur there due to their general distribution and lack of information on their introduction into the region. We found 14 such misreported species in the literature, mostly of the Nearctic and Neotropical origin. Our revised checklist contains 149 species, of which 19 have only generally been reported as occurring in Iran (without attribution to provinces). The ladybird fauna of the different Iranian provinces has been studied very unevenly, with the number of reported species ranging from 7 (Bushehr) to 59 (Fars).